Stopping the “Virus of the Gypsy Emptiness”: Racialization of the Bulgarian Roma During the Covid-19 Pandemic in Bulgaria - Salvatore, Camilla (Lidé města, 2023)
In Bulgaria, such as in many other European countries, the so-called “Gypsy/Roma” are the target of the rhetoric of extreme right parties who are pointing at them as the main responsible for a situation of crisis and fueling hate between groups. With the beginning of the COVID-19 epidemic, the already existing tension between the majority of Bulgarians with non Roma origin and the so-called Tsigani has intensified and been fueled by political discourses that urge to “close the ghettos everywhere” (A. Dzhambaski, 18.03.2020) which have been translated into safety measures – such as closure, disinfection and introduction of a system of control access to the neighborhoods where the “population of Roma origin” is supposed to live. By analyzing an official discourse of this kind and comments and reactions to it, we will see how the stereotypes concerning Bulgarian Roma are legitimated by institutional voices that are alimenting antigypsism (Wippermann, 2005; Knudsen, 2005, Nicolae, 2006, Piasere, 2010; 2011). We will try to see these attitude as consisting in a semiotic process of categorization and enregistrement (Agha, 2007) through which particular features of individuals are identified as typical of the group they are supposed to belong to.